An Iterative Modeling and Validation Study of a Low-Cost Thyristor-Based Controlled Half-Wave Rectifier - Emon, Asif Eakball; Tabassum, Anika (PT. Teknologi Futuristik Indonesia, 2025)
The effective teaching of power electronics is critical for developing engineers capable of addressing global energy challenges, yet a persistent gap exists between idealized theoretical models and the non-ideal behavior of physical systems. This gap undermines both technical proficiency and conceptual understanding in engineering education. To address this, our study implemented and evaluated an iterative research and development methodology focused on a fundamental power conversion circuit: the controlled half-wave rectifier. The primary objective was to quantify the simulation-reality discrepancy and to assess whether a cyclical process of modeling, simulation, physical deployment, and data-driven refinement could serve as an effective pedagogical framework. Our key findings reveal a quantifiable performance gap, with a consistent 1.67V forward voltage drop in the silicon-controlled rectifier (SCR) leading to output deviations of up to 38% from theoretical predictions at low firing angles, as rigorously analyzed using Mean Absolute Percentage Error (MAPE) and Root Mean Square Error (RMSE). Crucially, this technical investigation was seamlessly integrated with experiential learning. The iterative methodology resulted in a measurable 40% average improvement in student troubleshooting skills and conceptual mastery, while the entire prototype was realized for under USD 12, demonstrating a commitment to accessible and sustainable design. The implications of this work are twofold: it provides educators with a validated, replicable blueprint for a hands-on curriculum that bridges theoretical and practical knowledge, and it offers engineers a model for cost-effective prototyping that acknowledges and integrates component non-idealities from the outset. This research confirms that closing the simulation-reality gap is not merely a technical necessity but a foundational element of responsible and effective engineering education.